DAMPAK LINGKUNGAN KERJA PADA KINERA PEGAWAI DI LINGKUNGAN BPJS KETENAGAKERJAAN KOTA JAMBI - Helencia, Kiki (Fakultas Hukum dan Ekonomi Bisnis, 2024)
The purpose of this research is to know the environmental condition of work and performance of employees at BPJS Ketenagakerjaan Kota Jambi and to know the impact of the working environment on the performance of employees at BPJS Ketenagakerjaan Kota Jambi. In discussing this issue authors use quantitative descriptive method that is by looking for information about the symptoms, clearly defined objectives to be achieved, plan the way of approach, collecting data as Materials to create a report. In this research the author held comparisons between environmental condition to the performance of employees in BPJS Ketenagakerjaan Kota Jambi. BPJS Ketenagakerjaan Kota Jambi as a government institution is responsible for the provision of services to the community in its working area. The provision of services to BPJS Ketenagakerjaan Kota Jambi is based on the awareness of the task, responsibility and high taste to carry out the good service so that people are satisfied. BPJS Ketenagakerjaan Kota Jambi is a Social Security program responsible for the state to provide social economic protection to the community. The constant value of 0.170 gives the meaning that if the working environment variable (X) is 0, then the performance variable (Y) is worth 0.170. Furthermore, with the simple linear regression equation above, there is a value of variable regression coefficient of work environment which is positive value of 0939. If the value of the working environment coefficient is positive if changes to the work environment variables will result in a directional change in the performance variable. In this study, it can be analyzed the magnitude of the working environment to the performance of 0939. This means that if the working environment of BPJS Ketenagakerjaan Kota Jambi increased by 1%, employees ' performance will increase by 93.9%. Working environment on BPJS high employment with an average score of 153.7. Furthermore, employee performance at BPJS Manpower is very high with an average score of 164.1. Based on the hypothesis test it is noted that there is a significant influence between working environment and employee performance in BPJS employment. This can is evidenced by the comparison between the calculated T value larger than t table (11,623 > 2,022). The working environment can affect performance by 77.6% and the remaining 22.4% is influenced by other variables not examined in this study.